Raton Day Tour One : Nearby adventures from Raton 1 - carroll, William; William Carroll (Raton, NM Coda Publications, 2008)
It's all here in less than a day's drive from Raton: New Mexico's Finest City. Yankee, a former coal mine village, ruins of the Sugarite Mine and then to lovely Lake Malya. Visit the Capulin volcano, unique in our nations, what's left of the nearby village, into Folsom for a tiny community fair, on to nearby hidden waterfalls and Branson, Colorado's annual garage sale. Finally visit Johnson mesa's lonely church and be home after sunset.
William Carroll.
93123
Keywords: William Carroll; Yankee Coal Mine; Sugarite Mine; Lake Maloya; Capulin Volcano; Folsom, NM; Branson, CO; Johnson Mesa, NM. -- Northeastern New Mexico; Raton, New Mexico -- Northeastern New Mexico